Acceptance and Commitment group Therapy for patients with multiple functional somatic syndromes: a three-armed trial comparing ACT in a brief and extended version with enhanced care. Issue 6 (26th June 2018) - Pedersen, Heidi Frølund; Agger, Johanne L.; Frostholm, Lisbeth; Jensen, Jens S.; Ørnbøl, Eva; Fink, Per; Schröder, Andreas
Abstract: Background: Psychological treatment for functional somatic syndromes (FSS) has been found moderately effective. Information on how much treatment is needed to obtain improvement is sparse. We assessed the efficacy of a brief and extended version of group-based Acceptance and Commitment Therapy (ACT) v. enhanced care (EC) for patients with multiple FSS operationalised as Bodily Distress Syndrome multi-organ type. Methods: In a randomised controlled three-armed trial, consecutively referred patients aged 20–50 with multiple FSS were randomly assigned to either (1) EC; (2) Brief ACT: EC plus 1-day workshop and one individual consultation; or (3) Extended ACT: EC plus nine 3-h group-based sessions. Primary outcome was patient-rated overall health improvement on the five-point clinical global improvement scale 14 months after randomisation. A proportional odds model was used for the analyses. Results: A total of 180 patients were randomised; 60 to EC, 61 to Brief ACT, and 59 to Extended ACT. Improvement on the primary outcome after Extended ACT was significantly greater than after EC with an unadjusted OR of 2.9 [95% CI (1.4–6.2), p = 0.006]. No significant differences were found between Brief ACT and EC. Of the 18 secondary outcomes, the only significant difference found was for physical functioning in the comparison of Extended ACT with EC. Conclusions: Patients rated their overall health status as more improved after Extensive ACT than after EC; however, clinically relevant secondary outcome measures did not support this finding. Discrepancies between primary and secondary outcomes in this trial are discussed.